Effect of high intensity laser in the treatment of myofascial trigger points in symptomatic knee osteoarthritis: A randomized single-blinded controlled trial - B. Ahmed , Bassant; Abu El Kasem, Shimaa T.; Al-Shenqiti, Abdullah M.; Morsy, Mona (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
Background: Osteoarthritis (OA) is one of the most prevalent causes of musculoskeletal pain and disability among the middle age and elderly population. It significantly affects the overall quality of life of the affected individuals. Objectives: To find out the impact of high intensity laser therapy (HILT) on myofascial trigger points (MTrPs) in symptomatic knee OA. Methods: This is a single-blinded pre–post randomized experimental trial. A total of 40 patients, both male and female, falling within the age group of 35-55 years, BMI 25–29.9 Kg/Cm2, diagnosed with bilateral knee osteoarthritis (grade 2), were recruited as participants of the study. All the participants were clinically evaluated for the signs and symptoms of myofascial pain, tenderness over the vastus medialis muscle and the medial head of the gastrocnemius muscle. The participants were randomly allocated into two groups with n=20 in each group. The participants of the experimental group received high-power laser therapy and underwent exercises on the MTrPS of the vastus medialis and the medial head of the gastrocnemius muscle. The participants of the control group received placebo laser "sham laser" and underwent exercises for the vastus medialis and the medial head of the gastrocnemius muscle. A blood cortisol level test, pressure algometer, digital electronic goniometer, and the KOOS-PS questionnaire were used to measure the pain level, pain threshold, knee ROM, and knee function. Outcome assessment was done at Day 0 and post intervention at the end of 4 weeks. Results: The MANOVA test revealed that both groups improved significantly in all parameters at week 4, with the HILT group improving more than the sham group in blood cortisol levels, pressure algometer measures, knee passive ROM, and KOOS scores (P < .05). Conclusion: HILT is an efficient approach in the treatment of MTrPs in knee OA.